Physical exercise and adolescent mental toughness: mediating effects of family support and socioeconomic status - Yuan, Weihan; Wang, Guihong; Wang, Zixian (Frontiers in Psychology, 2025)
BackgroundMental toughness refers to an individual’s capacity to respond positively to stress and frustration in social contexts, and it is considered a crucial aspect of mental health. Physical education is increasingly being recognized as an effective means of promoting psychological well-being among adolescents.ObjectivesThis paper explores the relationship between physical exercise and mental toughness in adolescents, examining the underlying mechanisms through the lenses of family support and socioeconomic status (SES).ResultsFindings from an analysis of an adolescent health database indicate that (1) physical exercise significantly enhances mental toughness (P < 0.001); specifically, increased duration and diversity of physical activity are associated with greater resilience to anxiety, depression, and hostility. (2) Family support (P < 0.001) plays a partial mediating role between physical exercise and mental toughness, indicating the mental health benefits of adolescents. (3) Physical exercise is not influenced by adolescents’ level of mental toughness through the mediating effect of SES (P > 0.05). (4) Consideration of other factors revealed that peer relationships (P < 0.001) emerged as an important mediating factor, highlighting the role of social interaction during physical exercise in fostering mental toughness and resilience among adolescents.ConclusionIn conclusion, this study demonstrates that regular physical exercise is positively associated with higher psychological resilience among adolescents, and this relationship is partially mediated by enhanced family support and better peer relationships. These findings underscore the importance of supportive family and peer environments in amplifying the beneficial effects of exercise on youth resilience, and they highlight the need for future longitudinal research and intervention efforts to confirm these causal pathways and extend the insights to broader populations.